A naphthalimide-derived fluorogenic probe for SNAP-tag with a fast record labeling rate. (December 2017) - Qiao, Qinglong; Liu, Wenjuan; Chen, Jie; Zhou, Wei; Yin, Wenting; Miao, Lu; Cui, Jingnan; Xu, Zhaochao
Abstract: SNAP-tag is one of most popular genetically encoded protein tags that can be labeled with fluorescent molecules for visualizing a protein of interest in live cells. Fluorogenic probes keep dark until they label protein tags, significantly improving the signal-to-noise ratio to image proteins without wash-out step. However, most of reported fluorogenic probes for SNAP-tag suffered from the low or mild labeling rate comparing with non-fluorogenic ones. In this paper, we reported a 4-amino-naphthliamide derived fluorogenic probe for SNAP-tag, which exhibited the fast record labeling rate among fluorogenic probes. Finally, we applied this probe to image proteins in mitochondria and nucleus in live cells without wash-out steps. Graphical abstract: The fluorogenic probe for SNAP-tag displayed a fast labeling rate. Highlights: The probe displayed a fluorescence turn-on response to label SNAP-tag. The probe exhibited the fast record labeling rate among known fluorogenic probes. The probe enables no-wash protein imaging in live cells.